Blake, Colour and the Truchsessian Gallery: Modelling the Mind and Liberating the Observer - Erle, Sibylle (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2008)
AbstractOn October 23, 1804, William Blake wrote to William Hayley: “Suddenly, on the day after visiting the Truchsessian Gallery of pictures, I was again enlightened with the light I enjoyed in my youth, and which has for exactly twenty years been closed from me as by a door and by window-shutters” (756). This article explores the significance of Blake’s delayed response to the viewing experience of the Truchsessian Gallery. It revisits the connections between Blake and Newton, optics, Locke and perception, and situates Blake’s understanding of colour and colour vision in its contemporary context; it investigates Blake’s account to Hayley and analyses some of the problematic representations of embodiment in the works done in the 1790s, arguing that the large colour prints demonstrate Blake’s awareness of the physical and optical qualities of colour.